Optimizing Learning Through Private Tutoring in Schools - Amalia Majid, Fitri (Journal of Education and Religious Studies, 2023)
This study explored the optimization of learning through private tutoring, analyzing its advantages, implementation, and impact on addressing students’ learning difficulties. Private tutoring had been shown to provide individualized attention, enhancing students’ motivation and comprehension of subject matter. Its implementation required careful planning and appropriate strategies, including the integration of technology and innovative learning media to support the learning process. The positive effects of private tutoring were reflected in students’ academic improvement, social development, and increased self-confidence. Moreover, this approach contributed to character building, equipping students to navigate future challenges. This study highlighted that with the right approach and support from all relevant stakeholders, private tutoring could serve as an effective strategy for improving educational quality and assisting students in overcoming learning difficulties.